Offspring of male rats exposed to binge alcohol exhibit heightened ethanol intake at infancy and alterations in T-maze performance. - Hollander, Jessica; McNivens, Megan; Pautassi, Ricardo M; Nizhnikov, Michael E (Alcohol, 2019)
Alcohol use is associated with a variety of negative consequences, including heightened likelihood of cognitive impairment, proclivity to alcohol use disorders (AUD), and alterations in the drinker's offspring. Children and rodents exposed to alcohol during pregnancy, or those whose fathers consumed alcohol prior to mating, often exhibit neurodevelopmental, physiological, and behavioral deficits. The present study assessed cognitive function and alcohol intake in male and female rats that were offspring of alcohol-exposed fathers. Adult male rats were exposed to alcohol or vehicle (0.0 or 2.0 g/kg, respectively; twice daily for 2 days followed by a rest day, for a total of eight alcohol or vehicle exposure days), or were left untreated and then mated with non-manipulated females. The offspring were assessed for alcohol intake, via intraoral infusion, followed by cognitive assessment via an alternating T-maze task. The results indicated that paternal ethanol exposure, prior to breeding, resulted in offspring that consumed significantly more ethanol than vehicle or untreated controls. Furthermore, the offspring of alcohol-exposed fathers exhibited a significant failure to initiate and complete the T-maze performance tests. Although, when they did engage in the tests they performed at the level of controls (i.e., 80% correct). The present results add to a growing body of literature suggesting that paternal pre-conception alcohol exposure can have deleterious effects on the offspring. Copyright © 2018 Elsevier Inc. All rights reserved.
11 citations (Crossref) [2023-10-31] Place: United States Hollander, Jessica. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. McNivens, Megan. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Pautassi, Ricardo M. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Electronic address: nizhnikovm1@southernct.edu.
Keywords: *Alcohol Drinking/px [Psychology]; *Binge Drinking/px [Psychology]; *Fathers/px [Psychology]; *Maze Learning/de [Drug Effects]; *Prenatal Exposure Delayed Effects/px [Psychology]; Alcohol Drinking; Alcohol intake; Animals; Article; Binge Drinking; Fathers; Female; Male; Maze Learning; Paternal alcohol exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; T-maze; T-maze test; adult; alcohol; alcohol consumption; animal; animal experiment; binge drinking; cognition; controlled study; dept.psy; drinking behavior; drug effect; father; female; male; maze test; nonhuman; paternal exposure; peer-reviewed; pregnancy; prenatal exposure; psychology; rat

Influence of prenatal pre-exposure to an odor on intake behavior of an aversive solution in newborn rats. - Kamenetzky, Giselle V; Suarez, Andrea B; Ifran, Maria Celeste; Nizhnikov, Michael E; Pautassi, Ricardo M (Neuroscience letters, 2018)
Early pre- or postnatal sensory experiences significantly influence flavor preference and food intake, and can induce liking for innately unpalatable flavors. Previous work found that newborn rats stimulated with an odor experienced shortly after birth exhibited heightened intake and seeking towards an artificial nipple containing quinine. This result suggests that odors made familiar trough early postnatal pre-exposure can shift the motivational value of unconditional stimuli. The objective of the current study was to assess the effect of an odor (lemon) experienced in-utero on the first intake responses towards an artificial nipple supplying quinine. The hypothesis, which was corroborated, was that stimulation with the olfactory stimulus experienced in-utero would increase the newborn's intake and grasp responses to the artificial nipple containing quinine. Exposure to the odor that had been pre-exposed in utero increased quinine intake and seeking (i.e., latency to grasp and total time in contact with the nipple, as well as number of and mean duration of nipple grasps) in 3-h-old pups. These results replicate those previously found with postnatal odor pre-exposure, and extend the phase for pre-exposure to the prenatal stage. Copyright © 2018 Elsevier B.V. All rights reserved.
5 citations (Crossref) [2023-10-31] Place: Ireland Kamenetzky, Giselle V. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Suarez, Andrea B. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Ifran, Maria Celeste. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Electronic address: MariaCeleste.Ifran@Alumnos.uai.edu.ar. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, United States. Pautassi, Ricardo M. Instituto de Investigacion Medica Mercedes y Martin Ferreyra, CONICET, Universidad Nacional de Cordoba, Cordoba, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, C.P 5000, Argentina.
Keywords: *Eating; *Feeding Behavior; *Odorants; *Prenatal Exposure Delayed Effects; *Quinine/ad [Administration & Dosage]; Animals; Animals; Newborn; Animals; Suckling; Article; Eating; Feeding Behavior; Female; Male; Neonate rat; Odor pre-exposure; Odorants; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal exposure; Quinine; Rats; Sprague-Dawley; Smell; Sprague Dawley rat; animal; animal experiment; aversive agent; controlled study; dept.psy; eating; feeding behavior; female; food intake; fragrance; learning; male; newborn; nipple; nonhuman; odor; peer-reviewed; pregnancy; prenatal exposure; priority journal; quinine; rat; smelling; stimulation; suckling animal

Change in the hedonic value of an aversive stimulus in the presence of a pre-exposed odor. - Kamenetzky, Giselle V; Suarez, Andrea B; Pautassi, Ricardo M; Mustaca, Alba E; Nizhnikov, Michael E (Physiology & behavior, 2015)
Rats exhibit a sensitive period from the time of birth until postnatal day 10 during which they develop preferences for odors even if those odors are paired with a moderately aversive stimulus. It is still unknown whether pre-exposure to an odor produces alterations on intake responses of basic tastants, and on other patterns that indicate a change in the hedonic value of reward, such as nipple grasping behavior. The current study assessed the effect of pre-exposure to an odor immediately after birth on intake responses of appetitive and aversive tastants. The objectives were to assess if 3-hour-old rats adjust their behaviors to obtain different values of appetitive and aversive rewards in the presence of a familiar odor. Specifically we wanted to determine whether the intake of saccharin or quinine, administered through the artificial nipple, increases in the presence of the familiar odor. Results showed that 3-hour-old rats differentially respond to two different concentrations of saccharin and two concentrations of quinine. In the presence of the pre-exposed odor newborn rats increased intake and grasp responses to the artificial nipple containing quinine. This effect disappeared with a higher concentration of quinine. These results suggest that the pre-exposed odor generated a change in the hedonic value of the aversive reward. Copyright © 2014 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Place: United States Kamenetzky, Giselle V. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Electronic address: yoselevich@hotmail.com. Suarez, Andrea B. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Pautassi, Ricardo M. Instituto de Investigacion Medica Mercedes y Martin Ferreyra, CONICET, Universidad Nacional de Cordoba, Cordoba, Argentina. Mustaca, Alba E. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Nizhnikov, Michael E. Southern Connecticut State University, United States.
Keywords: *Avoidance Learning/ph [Physiology]; *Conditioning; Psychological/ph [Physiology]; *Discrimination; Psychological/ph [Physiology]; *Emotions/ph [Physiology]; *Odorants; *Smell/ph [Physiology]; Age Factors; Analgesics; Non-Narcotic; Animals; Animals; Newborn; Appetitive Behavior; Appetitive Behavior/ph [Physiology]; Article; Aversive solutions; Avoidance Learning; Conditioning (Psychology); Discrimination (Psychology); Dose-Response Relationship; Drug; Emotions; Female; Male; Newborn rats; Odors; Olfactory learning; Ontogeny; Quinine; Quinine/ad [Administration & Dosage]; Rats; Rats; Sprague-Dawley; Reaction Time; Reaction Time/de [Drug Effects]; Reaction Time/ph [Physiology]; Saccharin; Saccharin/ad [Administration & Dosage]; Smell; Sprague Dawley rat; Sweetening Agents; age; analgesic agent; animal; animal behavior; animal experiment; appetite; aversion; avoidance behavior; birth; bitter taste; conditioning; controlled study; dept.psy; dose response; drug effects; emotion; exposure; female; food intake; grip strength; gustatory system; male; newborn; nipple; nonhuman; odor; peer-reviewed; perceptive discrimination; physiology; priority journal; quinine; rat; reaction time; reward; saccharin; stimulus; sweetening agent; taste